Aluminum alloy battery frame for electric vehicle and preparation method thereof

By using 6000 series aluminum alloy material and hot extrusion process to prepare the battery frame, combined with uniform annealing, extrusion and aging strengthening treatment, the problem of strength and toughness loss of battery frame under high temperature conditions is solved, and the effects of high strength, high toughness and high thermal stability are achieved.

CN116377291BActive Publication Date: 2025-03-18江苏友升汽车科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310196466.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2025-03-18
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

Existing battery frames are prone to loss of strength and toughness under high temperature conditions, and are difficult to meet the requirements of high thermal stability and resistance to lateral impact deformation.

Method used

The battery frame was prepared by hot extrusion process using 6000 series aluminum alloy material, and the mass ratio of Cu and Mg was controlled <2.6, and elements such as Cr, Mn, Ti, Zr were added to perform uniform annealing, extrusion and aging strengthening treatment.

Benefits of technology

The battery frame is achieved with high strength, high toughness and high thermal stability, and can maintain strength after baking in high temperature and short cycles, and the strength loss is small after baking in low temperature and long cycles, meeting the requirements of resistance to lateral impact deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116377291B_ABST
    Figure CN116377291B_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum alloy battery frame for electric vehicles and a preparation method thereof. The weight percentages of the components of the aluminum alloy are as follows: Si: 0.75-0.80%, Fe: ≤0.15%, Cu: 0.10-0.15%, Mn: 0.45-0.50%, Mg: 0.58-0.63%, Cr: 0.10-0.15%, Zn: ≤0.10%, Ti: 0.03-0.05%, Zr: 0.05-0.1%, and the balance is Al. The battery frame is obtained by smelting, alloying, degassing and deslagging, casting, homogenizing, extruding and aging the aluminum alloy. The battery frame can meet the following requirements: 1) tensile strength ≥305MPa, yield strength ≥280MPa, elongation ≥13%; 2) there is no loss of strength after short-term baking at 205°C for 1h, and the strength loss is within 10MPa after long-term baking at 150°C for 1000h; 3) the collision crush test meets the requirements of the three-peak curve, the energy absorption is ≥30KJ, and the cracking form is uniform without breakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum alloy processing, specifically relates to the technical field of automobile aluminum alloy battery frames, and in particular relates to an electric vehicle aluminum alloy battery frame and a preparation method thereof. Background Art

[0002] Lightweight technology is a basic technology that spans the development of automobiles. By optimizing the battery pack frame support structure to achieve lightweight body, it has become the development direction of the new energy vehicle industry. Figure 1 As the carrier of the power battery, it plays a key role in the safe operation and protection of the battery module. Especially when the vehicle collides, the battery frame needs to have excellent resistance to lateral impact deformation.

[0003] In order to solve the above technical problems, many useful explorations have been made in the prior art, but most of them are concentrated on the improvement of processing molds: for example, the Chinese utility model patent with announcement number CN214920405U is designed to solve the problem that the cross-section of the battery frame is complex, the 6061 material used has high metal strength and poor fluidity, resulting in poor forming state, and a sunken center back hole is used; the feed hole adopts small holes according to the shape of the product, and multiple holes balance the metal flow of each part; a protective step is designed to solve the technical problem that the oblique ribs in the center of the product are difficult to feed and easy to crack due to pressure. The Chinese invention patent with publication number CN112692095A is aimed at the technical problem of how to extrude the bottom plate profile of the battery tray with a width-to-thickness ratio of more than 130, and how to control the flatness within the range of 0.5mm without undergoing a shaping process, and how to ensure that the mold has a reasonable effective life. By using four auxiliary bridges to make a 50° inclined-pull design for the main bridge inlet, the mold strength can be improved and the stability of the profile discharge can be ensured; at the same time, the feed port is sunken by 25mm, which not only reduces the mold pressure and makes the profile discharge stable, but also controls the profile flatness within 0.2mm, and the mold life is also significantly improved.

[0004] In addition to the above-mentioned structural improvements to ensure accuracy, it is also required that the high-temperature spraying of the battery frame during the assembly stage and the exothermic baking conditions of the battery pack during driving will not cause loss of high strength and high toughness, so as to ensure the safety of the vehicle body. Summary of the invention

[0005] The present invention is directed to the above technical problems and provides an aluminum alloy battery frame for electric vehicles and a preparation method thereof. The present invention improves the composition of the aluminum alloy material, and the battery frame hot-extruded using the aluminum alloy material has high strength, high toughness and high thermal stability. In order to achieve the above objectives, the technical solutions adopted by the present invention are as follows:

[0006] In a first aspect, the present invention provides an aluminum alloy battery frame for an electric vehicle, which is made of a 6000 series aluminum alloy, wherein the weight percentages of the components of the aluminum alloy are as follows: Si: 0.75-0.80%, Fe: ≤0.15%, Cu: 0.10-0.15%, Mn: 0.45-0.50%, Mg: 0.58-0.63%, Cr: 0.10-0.15%, Zn: ≤0.10%, Ti: 0.03-0.05%, Zr: 0.05-0.1%, and the balance is Al.

[0007] Preferably, the material components of the aluminum alloy battery frame of the electric vehicle of the present invention are selected from any of the following situations:

[0008] (1) Si: 0.786%, Fe: 0.125%, Cu: 0.122%, Mn: 0.488%, Mg: 0.608%, Cr: 0.121%, Zn: 0.011%, Ti: 0.032%, Zr: 0.069, balance Al.

[0009] (2) Si: 0.774%, Fe: 0.123%, Cu: 0.128%, Mn: 0.481%, Mg: 0.611%, Cr: 0.124%, Zn: 0.012%, Ti: 0.035%, Zr: 0.073, balance Al.

[0010] (3) Si: 0.775%, Fe: 0.121%, Cu: 0.129%, Mn: 0.478%, Mg: 0.621%, Cr: 0.121%, Zn: 0.011%, Ti: 0.033%, Zr: 0.071, balance Al.

[0011] (4) Si: 0.781%, Fe: 0.121%, Cu: 0.125%, Mn: 0.483%, Mg: 0.615%, Cr: 0.121%, Zn: 0.011%, Ti: 0.033%, Zr: 0.069, balance Al.

[0012] (5) Si: 0.783%, Fe: 0.122%, Cu: 0.122%, Mn: 0.482%, Mg: 0.613%, Cr: 0.122%, Zn: 0.011%, Ti: 0.035%, Zr: 0.068, balance Al.

[0013] (6) Si: 0.784%, Fe: 0.121%, Cu: 0.125%, Mn: 0.483%, Mg: 0.610%, Cr: 0.121%, Zn: 0.012%, Ti: 0.033%, Zr: 0.072, balance Al.

[0014] The second aspect of the present invention provides a method for preparing the above-mentioned aluminum alloy battery frame of an electric vehicle, comprising the following steps:

[0015] (1) Melting: Add primary recycled materials and aluminum ingots to the melting furnace according to the formula ratio, where the recycled materials ratio is ≤30%; recycled materials refer to the sawing ends of profiles with the same chemical composition produced by extrusion, free of oil, aluminum chips, soil and other impurities.

[0016] (2) Alloying: When the temperature of aluminum liquid in the smelting furnace reaches 740-760℃, alloy elements are added in proportion after slag removal, and electromagnetic stirring is turned on to ensure uniform composition;

[0017] (3) Degassing and slag removal: The aluminum liquid undergoes three refining processes to remove hydrogen and impurities from the aluminum liquid;

[0018] (4) Casting: After the aluminum liquid is allowed to stand, it is drained and passed through aluminum titanium boron wire for grain refinement, box-type degassing, deep bed filtration, and finally cast into aluminum rods through a casting system;

[0019] (5) Homogenization treatment: After the aluminum rod is cast, it is sent to a homogenization furnace for homogenization annealing treatment;

[0020] (6) Extrusion: Extruding the homogenized aluminum rod into the required profile;

[0021] (7) Aging: After the extruded profile is parked for 24 hours, it enters the aging furnace for aging strengthening.

[0022] Among them, steps (1) to (3) are conventional technical means in the art and will not be described in detail. The specific process conditions in steps (4) to (7) are as follows:

[0023] In step 4, the casting is completed in the hot top tooling, using a low temperature, medium speed, and large water volume casting process: the aluminum liquid temperature is controlled at 680-690°C, the casting speed is 85-90mm / min, and the cooling water flow rate is 360-380m3 / h, so that the aluminum bar surface has a slight cold shut defect;

[0024] In step 5, the specific conditions of the homogenization process are as follows: the aluminum rod is heated to 570-575°C, kept at this temperature for 1 hour, then cooled to 550-555°C, kept at this temperature for 14 hours, and then quickly cooled by spraying water after being taken out of the furnace;

[0025] In step 6, the specific conditions of the extrusion process are as follows: the aluminum rod is heated to 520-525°C, cooled to 480-485°C by wind and mist within 2 minutes, and extruded into the extrusion barrel at an extrusion speed of 2.6±0.2mm / s. The outlet temperature is controlled at 545-560°C, and a water spray quenching process is used, requiring the temperature after cooling to be ≤60°C.

[0026] In step 7, the specific conditions of the aging process are as follows: the extruded profile is placed at room temperature for 24 hours and then subjected to double-stage aging treatment, after being kept at 170±3°C for 6 hours, the temperature is further raised to 205±3°C and kept for 3 hours, and then naturally cooled after being taken out of the furnace.

[0027] The beneficial technical effects of the present invention are as follows:

[0028] 1) The Cu content is controlled at 0.10-0.15%, the Mg content is controlled at 0.58-0.63%, and the mass ratio of Cu to Mg is controlled to be less than 2.6. Cu plays a solid solution strengthening effect, and Cu and Mg mainly form S (Al2CuMg) phase with Al, and its transition phase has excellent thermal stability.

[0029] 2) The Cr content is 0.10-0.15%, which can prevent solute aggregation and precipitate coarsening during the aging process. At the same time, Mn is controlled at 0.40-0.45%. The two can have a strong solid solution strengthening effect, which is beneficial to resist the performance loss of high-temperature short-cycle baking. In addition, it can inhibit the recrystallization process and obtain a fine fibrous grain structure, which is beneficial to plastic deformation.

[0030] 3) Adding a small amount of Ti and Zr elements can make Zr, Ti and B in the alloy form (Ti, Zr) B2 composite particles and precipitate at the grain boundaries. This composite particle has a high melting point and high hardness, and can play a role in aging hardening when baked at low temperature for a long period of time.

[0031] 4) During the casting process, low-temperature and large-volume casting is used to increase the solid solubility of the Mg2Si phase in the aluminum rod, reduce the segregation degree of the core of the aluminum rod, and improve the grain boundary stability of the cast aluminum rod. At the same time, a low-temperature and long-term homogenization process is used to effectively improve the diffusion uniformity of the Cu element and reduce the segregation of the Cu element.

[0032] 5) The extrusion process uses a method of rapidly cooling the high rod temperature to the normal rod temperature before extrusion into the barrel, which can increase the degree of pre-solid solution of the alloy. Combined with the subsequent two-stage aging process, a large number of dispersed precipitation strengthening phases can be formed.

[0033] The battery frame made of the above aluminum alloy can meet the following requirements:

[0034] 1) Tensile strength ≥305MPa, yield strength ≥280MPa, elongation ≥13%;

[0035] 2) After short-term baking at 205°C for 1 hour, there is no loss in strength; after long-term baking at 150°C for 1000 hours, there is a loss in strength within 10MPa;

[0036] 3) The collision crush test meets the requirements of the three-peak curve, the energy absorption is ≥30KJ, and the cracking form is uniform without breakage. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a schematic diagram of the structure of the aluminum alloy battery frame of an electric vehicle. DETAILED DESCRIPTION

[0038] The present invention is now described in detail in conjunction with the embodiments and the accompanying drawings, but it should be understood that the specific description below is illustrative rather than restrictive, and should not be used to limit the protection scope of the present invention.

[0039] 1. Aluminum rod components and preparation

[0040] The ingredients of Examples 1 to 6 are shown in Table 1, and then the aluminum bars with the corresponding ingredients are obtained through smelting, alloying, degassing and deslagging, and casting:

[0041] Table 1 Composition of aluminum rods in Examples 1 to 6

[0042]

[0043] The preparation process of the aluminum rod in the above embodiment is as follows:

[0044] (1) Melting: Add primary recycled materials and aluminum ingots into the melting furnace according to the formula ratio, where the recycled materials ratio is ≤30%;

[0045] (2) Alloying: When the temperature of aluminum liquid in the smelting furnace reaches 740-760℃, alloy elements are added in proportion after slag removal, and electromagnetic stirring is turned on to ensure uniform composition;

[0046] (3) Degassing and slag removal: The aluminum liquid undergoes three refining processes to remove hydrogen and impurities from the aluminum liquid;

[0047] (4) Casting: After the aluminum liquid is allowed to stand, it is drained and passed through aluminum titanium boron wire grain refinement, box-type degassing, deep bed filtration, and finally cast into aluminum rods through the casting system. The details are as follows: After the hot top tooling is completed, a low-temperature, medium-speed, and large-water casting process is adopted: the aluminum liquid temperature is controlled at 680-690℃, the casting speed is 85-90mm / min, and the cooling water flow rate is 360-380m 3 / h, so that the aluminum bar surface has slight cold shut defects;

[0048] (5) Homogenization treatment: After the aluminum rod is cast, it is sent to a homogenization furnace for homogenization annealing treatment, which is as follows: the aluminum rod is heated to 575°C and kept at this temperature for 1 hour, then cooled to 550°C, kept at this temperature for 14 hours, and then quickly cooled by spraying water;

[0049] (6) Extrusion: The homogenized aluminum rod is extruded into the required profile as follows: the aluminum rod is heated to 525°C, cooled to 485°C by wind and mist within 2 minutes, and then extruded into the extrusion barrel at an extrusion speed of 2.6 mm / s and an outlet temperature of 545-550°C. The quenching process is performed by water spraying, and the temperature after cooling is ≤60°C.

[0050] (7) Aging: After the extruded profile is parked for 24 hours, it enters the aging furnace for aging strengthening. The details are as follows: After the extruded profile is parked at room temperature for 24 hours, it is subjected to a double-stage aging treatment, which is kept at 170°C for 6 hours and then continued to be heated to 205°C for 3 hours. After being taken out of the furnace, it is naturally cooled.

[0051] 2. Performance Test

[0052] The aluminum bars in Examples 1 to 6 were subjected to the following tests: (1) T6 mechanical properties; (2) mechanical properties after short-term baking at 205°C for 1 h; (3) mechanical properties after baking at 150°C for 1000 h; (4) column impact crushing data in the T6 state.

[0053] Table 2 lists the T6 mechanical performance parameters of Examples 1 to 6; Table 3 lists the mechanical performance parameters of Examples 1 to 6 after short-cycle baking at 205°C for 1h; Table 4 lists the mechanical performance parameters of Examples 1 to 6 after baking at 150°C for 1000h; Table 5 lists the column impact crushing data of Examples 1 to 6 in the T6 state. Rm represents tensile strength, RP0.2 represents yield strength, A represents elongation, and Ak represents absorbed work. The details are as follows:

[0054] Table 2 Mechanical properties of aluminum rod T6 from Example 1 to Example 6

[0055]

[0056]

[0057] Table 3 Mechanical properties of aluminum bars from Example 1 to Example 6 after short-term baking at 205°C for 1h

[0058]

[0059] Table 4 Mechanical properties of aluminum bars from Example 1 to Example 6 baked at 150°C for 1000h

[0060]

[0061]

[0062] Table 5 Column impact crushing data of aluminum bars in T6 state in Examples 1 to 6

[0063]

[0064] According to the above data, the 6000 series aluminum alloy battery frame of the present invention has excellent properties of high strength, high toughness and high thermal stability.

[0065] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. An aluminum alloy battery frame for an electric vehicle, characterized in that: The weight percentages of the components of the aluminum alloy are as follows: Si: 0.75-0.80%, Fe: ≤0.15%, Cu: 0.10-0.15%, Mn: 0.45-0.50%, Mg: 0.58-0.63%, Cr: 0.10-0.15%, Zn: ≤0.10%, Ti: 0.03-0.05%, Zr: 0.05-0.1%, and the balance is Al. The preparation method of the aluminum alloy battery frame of the electric vehicle comprises the following steps: (1) Melting: Add primary recycled materials and aluminum ingots into the melting furnace according to the formula ratio. ≤30%; (2) Alloying: When the temperature of aluminum liquid in the smelting furnace reaches 740-760℃, alloy elements are added in proportion after slag removal, and electromagnetic stirring is turned on to ensure uniform composition; (3) Degassing and slag removal: The aluminum liquid undergoes three refining processes to remove hydrogen and impurities from the aluminum liquid; (4) Casting: After the aluminum liquid is allowed to stand, it is drained and passed through aluminum titanium boron wire for grain refinement, box-type degassing, deep bed filtration, and finally cast into aluminum rods through a casting system; (5) Homogenization treatment: After the aluminum rod is cast, it is sent to a homogenization furnace for homogenization annealing treatment; (6) Extrusion: Extruding the homogenized aluminum rod into the required profile; (7) Aging: After the extruded profile is parked for 24 hours, it enters the aging furnace for aging strengthening. In step (4), the casting is completed in a hot top tooling, using a low temperature, medium speed, and large water volume casting process: the aluminum liquid temperature is controlled at 680-690°C, the casting speed is 85-90mm / min, and the cooling water flow rate is 360-380m 3 / h, resulting in slight cold shut defects on the surface of the aluminum bar. In step (5), the specific conditions of the homogenization process are as follows: the aluminum rod is heated to 570-575°C, kept at this temperature for 1 hour, then cooled to 550-555°C, kept at this temperature for 14 hours, and then quickly cooled by spraying water. In step (6), the specific conditions of the extrusion process are as follows: the aluminum rod is heated to 520-525°C, cooled to 480-485°C by wind and mist within 2 minutes, and extruded into the extrusion barrel at an extrusion speed of 2.6±0.2mm / s. The outlet temperature is controlled at 545-560°C. A water spray quenching process is used, and the temperature after cooling is required to be ≤60°C. In step (7), the specific conditions of the aging process are as follows: the extruded profile is placed at room temperature for 24 hours and then subjected to a double-stage aging treatment. After being kept at 170±3°C for 6 hours, the temperature is further raised to 205±3°C and kept for 3 hours, and then naturally cooled after being taken out of the furnace.

2. The aluminum alloy battery frame for electric vehicles according to claim 1, characterized in that: The material components of the aluminum alloy battery frame of the electric vehicle are selected from any of the following situations: (1) Si: 0.786%, Fe: 0.125%, Cu: 0.122%, Mn: 0.488%, Mg: 0.608%, Cr: 0.121%, Zn: 0.011%, Ti: 0.032%, Zr: 0.069%, balance Al; (2)Si: 0.774%, Fe: 0.123%, Cu: 0.128%, Mn: 0.481%, Mg: 0.611%, Cr: 0.124%, Zn: 0.012%, Ti: 0.035%, Zr: 0.073%, balance Al; (3) Si: 0.775%, Fe: 0.121%, Cu: 0.129%, Mn: 0.478%, Mg: 0.621%, Cr: 0.121%, Zn: 0.011%, Ti: 0.033%, Zr: 0.071%, balance Al; (4) Si: 0.781%, Fe: 0.121%, Cu: 0.125%, Mn: 0.483%, Mg: 0.615%, Cr: 0.121%, Zn: 0.011%, Ti: 0.033%, Zr: 0.069%, the balance is Al; (5) Si: 0.783%, Fe: 0.122%, Cu: 0.122%, Mn: 0.482%, Mg: 0.613%, Cr: 0.122%, Zn: 0.011%, Ti: 0.035%, Zr: 0.068%, the balance is Al; (6) Si: 0.784%, Fe: 0.121%, Cu: 0.125%, Mn: 0.483%, Mg: 0.610%, Cr: 0.121%, Zn: 0.012%, Ti: 0.033%, Zr: 0.072%, the balance is Al.

Citation Information

Patent Citations

  • Battery frame bottom plate extrusion die

    CN112692095A

  • Extrusion die for high-strength alloy battery frame of new energy automobile

    CN214920405U

  • 6xxx-series aluminium alloy forging stock material and method of manufacting thereof

    CN109415780A

  • High-performance low-carbon secondary aluminum extruded profile and preparation method thereof

    CN115261649A